Funding America’s Nonprofits - Jennifer Ceema Samimi (Columbia Social Work Review, 2019)
Private nonprofits are increasingly relied upon to provide social services in the United States. As these nonprofits professionalize and look to the government and foundations to fund their work, communities may be deprived of services they need in order for the agendas of funders to be carried out. By examining the rise of the nonprofit as an institution in the United States, this article examines how social justice has been separated from social service provision by the system that has come to be known as the Nonprofit Industrial Complex.